2018
DOI: 10.1111/rec.12868
|View full text |Cite
|
Sign up to set email alerts
|

DNA metabarcoding—a new approach to fauna monitoring in mine site restoration

Abstract: Ecological restoration of landscapes is an integral part of the mining process. However, restoration is often constrained by a lack of consistent monitoring approaches. For example, the need for specialist techniques and trapping approaches often limits monitoring of fauna recovery. Application of molecular tools has made important contributions to understanding factors influencing restoration success. Here, we outline advances in next-generation sequencing methods, especially metabarcoding of environmental DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 109 publications
1
42
0
1
Order By: Relevance
“…plasticity (Demes, Graham, & Suskiewicz, 2009;Weigand, Jochum, Pfenninger, Steinke, & Klussmann-Kolb, 2011), (b) juveniles with ambiguous morphology (Ji et al, 2013;Richard et al, 2010), and (c) taxa having different levels of detectability according to season and time (Fernandes et al, 2018;Thompson & Newmaster, 2014).…”
mentioning
confidence: 99%
“…plasticity (Demes, Graham, & Suskiewicz, 2009;Weigand, Jochum, Pfenninger, Steinke, & Klussmann-Kolb, 2011), (b) juveniles with ambiguous morphology (Ji et al, 2013;Richard et al, 2010), and (c) taxa having different levels of detectability according to season and time (Fernandes et al, 2018;Thompson & Newmaster, 2014).…”
mentioning
confidence: 99%
“…This is not surprising as previous evidence has shown that land use history or subsequent secondary growth can create changes and differences in the soil decomposer communities that develop under these conditions due to changes in resource input 42 . Moreover, a study using DNA metabarcoding of arthropod orders showed that certain groups of invertebrates were significantly different across land use types in southwest China 43 . In terms of taxonomic resolution, the soil invertebrate community composition at the ESV level was distinctly different across the primary and secondary forests, compared to differences at class, order, and family resolutions.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing call to monitor restoration using the latest molecular approaches (Williams et al 2014;Fernandes et al 2018) but our findings suggest care must be taken in assay selection and optimization to ensure that target groups are identified. Examining fine scale changes to invertebrate communities may be an effective predictor for restoration success.…”
Section: Will a Dna Approach Improve Restoration Monitoring?mentioning
confidence: 96%